Aggregate patterns of macrofaunal diversity: An interocean comparison. Issue 7 (27th April 2017) - Defeo, Omar; Barboza, Carlos A. M.; Barboza, Francisco R.; Aeberhard, William H.; Cabrini, Tatiana M. B.; Cardoso, Ricardo S.; Ortega, Leonardo; Skinner, Viviane; Worm, Boris
Abstract: Aim: While geographical patterns of species richness are reasonably well explored for single well‐studied taxa, less is known about aggregate patterns of total richness for major biomes and their environmental correlates. Here we analyse continental‐scale aggregate patterns of macrofaunal diversity for sandy beaches, a dominant habitat along the Atlantic and Pacific coasts of South America. Location: South American coastlines. Time period: Present day (data amassed from studies performed since 1971). Major taxa studied: Benthic macrofauna, including crustaceans, polychaetes and molluscs. Methods: We compiled richness information for all macrofaunal groups on 263 sandy beaches in South America using standard criteria. We further matched these data with environmental variables including sea surface temperature (SST), chlorophyll a, grain size, beach slope, tide range and various morphometrics. We used generalized linear mixed models to relate environmental factors to observed variation in total macrofaunal richness across all beaches, testing competing hypotheses about environmental correlates and possible drivers of latitudinal diversity. Results: Macrofaunal richness decreased from tropical to temperate beaches in the Pacific and followed a parabolic trend in the Atlantic, with the highest biodiversity found at tropical and mid‐latitudinal bands. Beach slope, tidal range and chlorophyll a mostly explained latitudinal trends in macrofaunal richness, followed by grain size, SST and ocean basin. Main conclusions: This study indicates that richness of macrofaunal species at a given beach is most closely related to characteristics of the physical habitat, such as beach slope, area and grain size. At this scale, planktonic food supply also appeared to be more important than temperature, which is a dominant explanatory variable of global‐scale variation in species richness.